Approach for a sustainable process chain in manufacturing of fasteners for mechanical joining - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Materials Research Proceedings, 2023)

Controlled Rivet Deformation During Self-piercing Riveting Through a Tailored Strength Distribution Within the Rivet Material - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Proceedings of the 14th International Conference on the Technology of Plasticity - Current Trends in the Technology of Plasticity. ICTP 2023. Lecture Notes in Mechanical Engineering., 2023)

Corrosion behaviour of self-piercing riveted joints with uncoated rivets in high nitrogen steel - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering, 2024)

Cross-process chain influence of process variations in self-piercing riveting with regard to semi-finished product dimensions - Kuball, Clara-Maria; Uhe, Benedikt; Meschut, Gerson; Merklein, Marion (Journal of Advanced Joining Processes, 2024)

Development of a novel in-situ measurement method for thermo-mechanically coupled material characterization of high-strength aluminum alloys - Rigas, Nikolaos; Garcin, Thomas; Kuball, Clara-Maria; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2023)
High-strength aluminum alloys are more and more used for safety and crash-relevant components due to their advantageous density-to-strength ratio. By using thermal-supported forming strategies, failure-free deep drawing is possible for these materials. In this context, the hot form quench process (HFQ®) has shown to be a promising thermally-assisted forming strategy. By using locally tempered forming tools, the production of tailored components with different mechanical properties is possible. However, material characterization and process design with conventional characterization methods are quite challenging in this context. A new approach is the use of ultrasound-assisted material characterization in combination with a thermo-mechanical simulator. Thereby it is possible to perform an in-situ material characterization. So far, this technology is mainly used for steel materials. In this contribution, the potential of an adapted measurement strategy for high-strength aluminum alloys is presented. For this purpose, the influence of different measurement parameters on modified samples and the resulting measurement signal is investigated. With the help of this study, new standards are set for time-bound material characterization under thermo-mechanical stress. As a result, thermally-assisted forming methods can be designed more efficiently and faster in the futur

Grundlegende Untersuchungen zur umformtechnischen Herstellung von Halbhohlstanznieten aus hochverfestigenden Werkstoffen - Kuball, Clara-Maria (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2024)
Vor dem Hintergrund der Relevanz des Klimaschutzes hat die Transformation hin zu hocheffizienten, nachhaltigen Produktionsprozessen begonnen. Das Halbhohlstanznieten ist ein mechanisches Fügeverfahren, welches für die Realisierung von Leichtbau und Mischbauweisen von Bedeutung ist. Die Nietherstellung ist allerdings aufgrund der erforderlichen Wärmebehandlung und Beschichtung der Niete energie-, zeit- und kostenintensiv. Durch den Einsatz hochverfestigender nichtrostender Nietwerkstoffe wird die Nachbehandlung obsolet. Aufgrund der hohen Werkzeugbeanspruchung stellt die Umformung derartiger Stähle eine Herausforderung dar, weshalb ein umfassendes Prozessverständnis erforderlich ist. Das Ziel dieser Arbeit war daher die Erarbeitung eines grundlegenden Prozessverständnisses für die umformtechnische Herstellung von Nieten aus hochverfestigenden Werkstoffen. Schwerpunkte bildeten hierbei die Identifikation und Analyse von prozess- und werkstoffseitigen Einflussgrößen auf den Umformprozess und die Bauteileigenschaften. Dies erfolgte auf Basis eines kombinierten experimentell-numerischen Ansatzes. Der Machbarkeitsnachweis für die Herstellung von Nieten aus hochverfestigenden Werkstoffen wurde erbracht. Während bei konventionellen Nieten infolge der Wärmebehandlung homogene Eigenschaften vorliegen, weisen die neuen Nieten gradierte mechanische Eigenschaften auf. Somit wurde eine Ausgangsbasis für die Herstellung von Nieten mit für das Fügen maßgeschneiderten Eigenschaften geschaffe

Heating effect on the forming behaviour of high nitrogen steel in bulk forming - Kuball, Clara-Maria; Merklein, Marion (AIP Conference Proceedings, 2019)
As a result of the ongoing trend towards lightweight design in various industrial sectors like the automotive industry, mechanical joining methods become increasingly important. These methods make multi-material design possible, while thermic joining techniques reach their limits. Semitubular self-piercing riveting is a mechanical joining technology which allows joining dissimilar materials by using rivets as fasteners. The manufacturing of the rivets, however, is costly and time-consuming, as the rivets conventionally have to be hardened, tempered and coated after forming, in order to achieve adequate strength and corrosion resistance. By using high nitrogen steel for the rivets, these additional process steps are not necessary anymore. Hence, the rivet production becomes more efficient. Because of the strengthening, caused by strain hardening, high-strength parts can be produced by cold bulk forming of high-strength steels. Nevertheless, pressure-nitrided steels are still rarely used in cold bulk forming due to high tool loads, which is a major challenge for the manufacturing process. Under those circumstances, there is a need for new approaches to manufacturing with the aim of reducing the tool loads and realising the production of rivets made of pressure-nitrided steel. One possibility is forming at elevated temperatures below recrystallisation temperature. For this purpose, the influence of the temperature on the forming behaviour of high nitrogen steel is investigated. In this context, possible changes in nitrogen content caused by heating of the material and thereby induced negative effects on the material properties have to be evaluated. The results of compression tests at different temperatures demonstrate the distinct reduction of yield strength at elevated temperatures. Moreover, further investigations show that the heat treatment tends to result in a change of the nitrogen content determined using energy dispersive X-ray spectroscopy. However, the changing nitrogen content does not affect the strength of the heat treated material after cooling.
CRIS-Team Scopus Importer:2019-07-23

Hybrid process chains combining metal additive manufacturing and forming – A review - Hafenecker, Jan; Bartels, Dominic; Kuball, Clara-Maria; Kreß, Maximilian; Rothfelder, Richard; Schmidt, Michael; Merklein, Marion (CIRP Journal of Manufacturing Science and Technology, 2023)
Mass production of customized parts using conventional manufacturing technologies is challenging. The increasing use of hybrid approaches is a promising way to address mass customization. Due to the widespread use of the term hybrid in manufacturing technologies, the amount of literature is increasing dramatically. Therefore, this paper aims to provide an overview of the current state of the art on the combination of additive manufacturing (AM) and metal forming. First, the term hybrid is classified, followed by examples of hybrid AM. The focus of this paper is on the combination of either sheet metal forming or bulk metal forming with either powder bed fusion or directed energy deposition. Examples of both sequences - AM before or after forming - are presented and analyzed for their potential use in hybrid parts. From the selected literature, the possibilities of this approach are derived as well as the ongoing need for future research. AM offers great potential for adjusting the microstructure and resulting material properties to improve formability. Furthermore, forming operations need to be adapted to the different material properties found in hybrid part
Keywords: Hybrid manufacturing Hybrid processes Hybrid parts Additive manufacturing Sheet metal forming Bulk metal forming Review paper

Improvement of a rivet geometry for the self-piercing riveting of high-strength steel and multi-material joints - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering, 2020)
As a result of lightweight design, increased use is being made of high-strength steel and aluminium in car bodies. Self-piercing riveting is an established technique for joining these materials. The dissimilar properties of the two materials have led to a number of different rivet geometries in the past. Each rivet geometry fulfils the requirements of the materials within a limited range. In the present investigation, an improved rivet geometry is developed, which permits the reliable joining of two material combinations that could only be joined by two different rivet geometries up until now. Material combination 1 consists of high-strength steel on both sides, while material combination 2 comprises aluminium on the punch side and high-strength steel on the die side. The material flow and the stress and strain conditions prevailing during the joining process are analysed by means of numerical simulation. The rivet geometry is then improved step-by-step on the basis of this analysis. Finally, the improved rivet geometry is manufactured and the findings of the investigation are verified in experimental joining tests.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Aluminium; High-strength steel; Joining technology; Multi-material design; Rivet geometry; Self-piercing riveting

Increased Sustainability in Fastener Production with the Example of Self-Piercing Rivets - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Journal of Manufacturing and Materials Processing, 2023)

Influence of the process temperature on the forming behaviour and the friction during bulk forming of high nitrogen steel - Kuball, Clara-Maria; Jung, Robert; Uhe, Benedikt; Meschut, Gerson; Merklein, Marion (Journal of Advanced Joining Processes, 2020)

Influence of the process temperature on the tribological behaviour during bulk forming of high nitrogen steel - Kuball, Clara-Maria; Jung, Robert; Uhe, Benedikt; Meschut, Gerson; Merklein, Marion (1st International Conference on Advanced Joining Processes AJP 2019, 2019)

Influence of the rivet coating on the friction during self-piercing riveting - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Key Engineering Materials, 2021)

Mechanical joining of high-strength multi-material systems - trends and innovations - Merklein, Marion; Jäckisch, Manuel; Kuball, Clara-Maria; Römisch, David; Wiesenmayer, Sebastian; Wituschek, Simon (Mechanics & Industry, 2023)

Process-adapted temperature application within a two-stage rivet forming process for high nitrogen steel - Kuball, Clara-Maria; Uhe, Benedikt; Meschut, Gerson; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers Part L-Journal of Materials-Design and Applications, 2022)

Process design for the forming of semi-tubular self-piercing rivets made of high nitrogen steel. - Kuball, Clara-Maria; Uhe, Benedikt; Meschut, Gerson; Merklein, Marion (Procedia Manufacturing, 2020)
The aim to reduce pollutant emission has led to a trend towards lightweight construction in car body development during the last years. As a consequence of the resulting need for multi-material design, mechanical joining technologies become increasingly important. Mechanical joining allows for the combination of dissimilar materials, while thermic joining techniques reach their limits. Self-piercing riveting enables the joining of dissimilar materials by using semi-tubular rivets as mechanical fasteners. The rivet production, however, is costly and time-consuming, as the rivets generally have to be hardened, tempered and coated after forming, in order to achieve an adequate strength and corrosion resistance. A promising approach to improve the efficiency of the rivet manufacturing is the use of high-strength high nitrogen steel as rivet material because these additional process steps would not be necessary anymore. As a result of the comparatively high nitrogen content, such steels have various beneficial properties like higher strength, good ductility and improved corrosion resistance. By cold bulk forming of high nitrogen steels high-strength parts can be manufactured due to the strengthening which is caused by the high strain hardening. However, high tool loads thereby have to be expected and are a major challenge during the production process. Consequently, there is a need for appropriate forming strategies. This paper presents key aspects concerning the process design for the manufacturing of semi-tubular self-piercing rivets made of high-strength steel. The aim is to produce the rivets in several forming stages without intermediate heat treatment between the single stages. Due to the high strain hardening of the material, a two stage forming concept will be investigated. Cup-backward extrusion is chosen as the first process step in order to form the rivet shank without forming the rivet foot. Thus, the strain hardening effects in the area of the rivet foot are minimized and the tool loads during the following process step can be reduced. During the second and final forming stage the detailed geometry of the rivet foot and the rivet head is formed. In this context, the effect of different variations, for example concerning the final geometry of the rivet foot, on the tool load is investigated using multistage numerical analysis. Furthermore, the influence of the process temperature on occurring stresses is analysed. Based on the results of the investigations, an adequate forming strategy and a tool concept for the manufacturing of semi-tubular self-piercing rivets made of high-strength steel are presente
Keywords: high nitrogen steel; self-piercing riveting; joining by forming; bulk forming; tool design

Review on mechanical joining by plastic deformation - Meschut, Gerson; Merklein, Marion; Brosius, Alexander; Drummer, Dietmar; Fratini, Livan; Füssel, Uwe; Gude, Maik; Homberg, Werner; Martins, Paulo A. F.; Bobbert, Mathias; Lechner, Michael; Kupfer, Robert; et al. (Journal of Advanced Joining Processes, 2022)
Mechanical joining technologies are increasingly used in multi-material lightweight constructions and offer opportunities to create versatile joining processes due to their low heat input, robustness to metallurgical incompatibilities and various process variants. They can be categorised into technologies which require an auxiliary joining element, or do not require an auxiliary joining element. A typical example for a mechanical joining process with auxiliary joining element is self-piercing riveting. A wide range of processes exist which are not requiring an auxiliary joining element. This allows both point-shaped (e.g., by clinching) and line-shaped (e.g., friction stir welding) joints to be produced. In order to achieve versatile processes, challenges exist in particular in the creation of intervention possibilities in the process and the understanding and handling of materials that are difficult to join, such as fibre reinforced plastics (FRP) or high-strength metals. In addition, predictive capability is required, which in particular requires accurate process simulation. Finally, the processes must be measured non-destructively in order to generate control variables in the process or to investigate the cause-effect relationship. This paper covers the state of the art in scientific research concerning mechanical joining and discusses future challenges on the way to versatile mechanical joining processe
Keywords: Mechanical Joining; Joining processes; Pin-Joining; Clinching; Self-piercing riveting; Versatility

Selective application of different forming temperatures for individual process stages in a rivet manufacturing process with high nitrogen steel - Kuball, Clara-Maria; Uhe, Benedikt; Meschut, Gerson; Merklein, Marion (2nd International Conference on Advanced Joining Processes, 2021)

Self-piercing riveting using rivets made of stainless steel with high strain hardening - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Forming the Future - Proceedings of the 13th International Conference on the Technology of Plasticity. The Minerals, Metals & Materials Series., 2021)

Strength of self-piercing riveted joints with conventional rivets and rivets made of high nitrogen steel - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (ESAFORM 2021 - 24th International Conference on Material Forming, 2021)

Surface modification of additively manufactured parts by forming - Hafenecker, Jan; Kuball, Clara-Maria; Rothfelder, Richard; Schmidt, Michael; Merklein, Marion (ESAFORM 2021, 2021)
Additive manufacturing (AM) has many advantages compared to conventional processes. Of particular interest is the tool-less manufacturing of components, which allows one component to differ from the next completely and has the possibility of producing complex geometries. At the same time, however, AM has deficits such as long production times, low production tolerances and low surface qualities compared to conventional processes. Therefore, a finishing process using machining is often necessary, which extends the manufacturing time and produces waste. Thus, the avoidance of machining rework is of high interest, especially with expensive materials such as stainless steel or titanium. One approach to avoid machining processes is to use forming technology. By applying a forming operation, surfaces can be smoothened and geometrical aspects can be defined more sharply. Especially for functional surfaces, this procedure is favorable because of the work hardening, which in turn increases the strength of the material. Using the example of laser-based powder bed fusion (PBF-LB) followed by a cup backward extrusion process, two materials, which are frequently used in AM are investigated. On the one hand, the titanium alloy Ti-6Al-4V, as a material with low machinability and low formability at room temperature, and the stainless steel 316 L. Compared to Ti-6Al-4V, 316 L has a higher formability. Cylinders are built using PBF-LB and then formed to smoothen the surface and achieve a higher geometrical accuracy concerning edges. Formed, additively made parts have a more defined geometry, namely sharp edges and a surface roughness reduced by up to 90 %
Keywords: Additive Manufacturing; Forming; Surface Modification

Test method for friction characterization of rivets - Wituschek, Simon; Kuball, Clara-Maria; Merklein, Marion; Lechner, Michael (Defect and Diffusion Forum, 2020)
Due to continuously increasing requirements on lightweight sheet metal constructions, new processes and technologies are necessary to face current and future challenges. A trend in lightweight construction is the multi-material mix with sheets of different geometric and mechanical properties. To manufacture these so-called composite structures, new joining technologies and methods are required. One possibility is the further development of the self-pierce riveting joining process. For the simulation and evaluation of new and adapted processes of self-pierce riveting, numerical models are used to investigate process parameters and constraints. Besides precise material models for the numerical simulation of this joining process, the identification of friction parameters between the individual sheets and rivet elements is necessary to achieve exact results. Thus, a method is necessary to identify the friction coefficients between rivet elements and sheets. Such a method is presented and evaluated in this work. Different process parameters like the relative speed are varied for the experimental investigations and an analysis of the respective influence on the resulting friction coefficients is conducted. For the use of the test set-up, coefficients of friction are determined for rivet elements “RIVSET® C 5.3x5.5” (Böllhoff GmbH) coated with Almac® in combination with two different sheet materials HCT590X+Z and EN-AW 6014.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Friction; Joining; Self-piercing riveting